Psychopathy Deviate Tendency and Personality Characteristics in an Iranian Adolescents and Youth Sample: Gender Differences and Predictors - Khodarahimi, Siamak (European Journal of Mental Health, 2012)
The purpose of this research was to examine the possible effects of gender and age differences in psychopathy tendency and personality characteristics in an Iranian sample. The sample included 106 adolescents and 94 youth that were randomly selected from Eghlid city, Iran. Analysis indicated that psychopathy and personality were positively correlated in agreeableness and conscientiousness domains, and positive affects, intellectual interest and dependability traits among the adolescents and youth groups. Multivariate Analysis of Variance (MANOVA) rejected the effects of age group and gender in both psychopathy and personality characteristics. The resulting findings indicated that orderliness and positive affect, intellectual interest, extraversion and unconventionality, and orderliness explained psychopathy in the total sample, adolescents, youth and males respectively.